An Lp-Lq-Version of Morgan's Theorem for the n-Dimensional Euclidean Motion Group - Sihem Ayadi; Kamel Mokni (International Journal of Mathematics and Mathematical Sciences)
We establish an Lp-Lq-version of Morgan's theorem for the group Fourier transform on the n-dimensional Euclidean motion group M(n).